Staffing of Higher Educational Institutions of Ukraine in the Second Half of the XXth Century: Quality Assurance Issues - Iuliia Kuzmenko (Centre for Behaviour and Wellness Advocacy, 2017)
The importance of training researchers to provide quality higher education in Ukraine is an urgent need that cannot be ignored. As the world aims at attaining a golden age in education, it is crucial for countries like Ukraine to also take a second look at issues that may affect the quality of their education. The author reviewed educational regulations and analyzed some archival documents on educational policy regarding teachers' training and staffing of the Ukrainian Republic. It is remarkable that the ways of staffing higher educational establishments in the USSR between 1950 and 1990 revealed various successes and challenges of which, the Post-Soviet era today can learn from. It is important that future studies and policies look into how staffing issues affect the development of education in the independent Ukraine.